Rapporter - Dvinge, Anne; Hjortkjær, Jens; Bryder Steffensen, Astrid; Walther-Hansen, Mads; Krabbe, Niels; Nissen, Peter E.; Holme Hansen, Thomas; Kaargaard Nielsen, Steen; Krogh, Mads; Nygaard Pedersen, Inge; et al. (Danish Yearbook of Musicology, 2010)
Research Projects Jazz – a Cosmopolitan Vernacular: National and Transnational Narratives of Identity and Tradition (Anne Dvinge) A Cognitive Theory of Musical Tension (Jens Hjortkjær) Articulating Space – on the Interplay between Polyphonic Music and Gothic Architecture (Astrid Bryder Steffensen) Voices in Phonographic Space – a Theory about Vocal Staging in Modern Popular Music Recordings (Mads Walther-Hansen) Danish Centre for Music Publication (Niels Krabbe) Center for Songs and Ballads (Peter E. Nissen) Conferences Medieval and Renaissance Music Conference, Utrecht, 2009 (Thomas Holme Hansen) 6th International Conference on Music since 1900, Keele University, July 2009 (Steen Kaargaard Nielsen) IAML/IMS Conference, Amsterdam, July 2009 (Niels Krabbe) 15th Biennial IASPM International Conference: Popular Music Worlds, Popular Music Histories, Liverpool, July 2009 (Mads Krogh) 6th Nordic Music Therapy Conference: Sounding Relationships, Aalborg, 2009 (Inge Nygaard Pedersen and Lars Ole Bonde) Danish Musicological Society, 2009 (Anne Ørbæk Jensen)